Angiotensin-converting enzyme genotype affects skeletal strength in elite athletes - Matos Costa, A.; Silva, A. S.; Garrido N. D.; Louro, H.; Almeida Marinho, D.; Cardoso Marques, M.; Breitenfeld, L. (Journal of Sports Science & Medicine, 2009)
Previous studies have associated angiotensin-converting enzyme (ACE) D allele with variability in the skeletal muscle baseline strength, though conclusions have been inconsistent across investigations. The purpose of this study was to examine the possible association between ACE genotype and skeletal muscle baseline strength in elite male and female athletes involved in different event expertise. A group of 58 elite athletes, designated as Olympic candidates, were studied: 35 swimmers (19 males and 16 females, 18.8 ± 3.2 years) and 23 triathletes (15 males and 8 females, 18.7 ± 3.0 years). The athletes were classified as: short (< 200m) and middle (400m to 1500m) distance athletes, respectively. For each subject the grip strength in both hands was measure using an adjustable mechanical hand dynamometer. The maximum height in both squat jump (SJ) and counter movement jump (CMJ) were also assessed, using a trigonometric carpet (Ergojump Digitime 1000; Digitest, Jyvaskyla, Finland). DNA extraction was obtained with Chelex 100® and genotype determination by PCR-RFLP methods. Both males and females showed significantly higher right grip strength in D allele carriers compared to II homozygote's. We found that allelic frequency differs significantly by event distance specialization in both genders (p < 0.05). In fact, sprinter D allele carriers showed the superior scores in nearly all strength measurements (p < 0.05), in both genders. Among endurance athletes, the results also demonstrated that female D allele carriers exhibited the higher performance right grip and CMJ scores (p < 0.05). In conclusion, the ACE D allele seems associated with skeletal muscle baseline strength in elite athletes, being easily identified in females.